Using agent- and organisation-oriented programming to develop a team of agents for a competitive game - Hübner, Jomi F.; Bordini, Rafael H. (Annals of mathematics and artificial intelligence, 2010)
The multi-agent programming contest uses a cow-herding scenario where two teams of cooperative agents compete for resources against each other. We developed such a team of agents using two well-known platforms, one based on a logic-based agent-oriented programming language, called Jason , and the other based on an organisational model, called oise . While there is significant research on both agent programming and agent organisations, this was one of the first applications of a combined approach where we can program deliberative agents and organise them using a sophisticated organisational model. In this paper, we describe and discuss our contribution to the multi-agent contest using this combination of agent and organisation programming.